Determinación de las fracciones de carbono orgánico en el suelo del páramo La Cortadera, Boyacá (2016)
Páramos are considered strategic ecosystems because of their supply of environmental services, the accumulation of carbon being among those worth highlighting. This study aimed to determine the fractions of organic carbon present in the ground of the Páramo La Cortadera, employing the technique of organic matter characterization and the wet digestion method (Walkley – Black). The results showed that the native vegetation has a higher concentration of carbon compared to the coverings of farms and pastures; being that the carbon is extractable, the fraction that had the highest values, followed by humic and fulvic acids. The study concludes that the páramo “La Cortadera” is a very vulnerable ecosystem due to high anthropogenic impact, therefore, it is preferable to preserve and protect it, due to the fact that it contains labile carbon fractions that can be returned directly to the atmosphere, favoring climate change and the greenhouse effect.